Simultaneous Tissue Extraction and Quantification of Reproductive Neuropeptides and Sex Steroids in Zebrafish and Mouse - Lu, Chunyu (Université d'Ottawa / University of Ottawa, 2022)
The detection and quantification of hormones are important to assess the reproductive and stress status of experimental models and for the diagnosis of diseases in human and veterinary clinics. The peptide secretoneurin (SN) has been proposed as a new sex hormone, but effective quantification methods are challenging. Traditional methods require the use of antibodies with either radioactive or non-radioactive tracers. There are difficulties with these methods in terms of sensitivity, specificity, and inter-laboratory repeatability. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) can circumvent many of these challenges. Another source of variation is the extraction of lipophilic steroidal compounds, which is incompatible with the extraction of hydrophilic peptide hormones. I have developed efficient extraction and sensitive detection methods of SN with numerous other peptide and steroid hormones in the same tissue sample in mice and zebrafish. The extraction efficiency for both peptide and steroid analytes is over 85%. The standard deviation for extraction and LC-MS/MS analysis for each compound varies between 5-10%. The steroid hormones can be quantified in the low to medium fmol/µL range. We quantified peptide hormones in the high fmol/µL to low pmol/µL range. Mouse SN levels were measured and compared against the levels of GnRH 1, oxytocin, vasopressin, E2, and P4 in multiple tissues at 3 important periods through the estrous cycle. In addition, SN levels were found to be moderately related to GnRH 1 levels in the hypothalamus in the estrous cycle. This is important because it is GnRH 1 that stimulates the luteinizing hormone surge in the pituitary that regulates ovulation in all vertebrate species. I also determined that SNa and SNb were both within the 2-8 pmol/µL range in the brain or pituitary harvested from a single female zebrafish. This makes it feasible for the first time to study the correlation between the SNs and other peptides and steroid hormones by quantifying them simultaneously in very small tissue samples. Untargeted peptidomics determined that the SN peptides in zebrafish can be further processed into smaller discrete fragments. This implies not only active synthesis and selective peptide processing but suggests that the are unknown functions of the SN peptide fragments that await discovery. This cost-effective package was used for the detailed assessment of hypothalamic-pituitary-gonadal function in mice and zebrafish and may be adaptable to many other hormones across species.
Keywords: Secretoneurin; LC-MS/MS; Quantification; Hormone